A DASH 360° immersive video streaming control system. Issue 5 (15th June 2020) - Ribezzo, Giuseppe; De Cicco, Luca; Palmisano, Vittorio; Mascolo, Saverio
Abstract : This letter proposes a DASH‐compliant video streaming control system for 360 ° immersive videos. The overall system is composed of two control algorithms which cooperate both to adapt the video bitrate to match the time‐varying end‐to‐end network bandwidth and to select the most appropriate view of the panoramic scene in response to the varying point of view of the user. The proposed system has been implemented and an extensive experimental evaluation has been carried out in a realistic emulated network scenario to assess the obtainable performances in terms of visual quality and bitrate reduction.